DISTRIBUSI MAST CELL PADA MESENTERIUM TIKUS - N Ibrahim, Mohamad; Widjajanto, Edi; Rosita, Rita (Jurnal Kedokteran Brawijaya, 2008)
Mast cell are derived from haematopoietic progenitors in the bonemarrow. Developing mast cell subsequently migrate to peripheral tissues, such as the skin, mucosa and air way, where they terminate their differentiation under  the  influence  of  factors  in  the  tissue  micro-enviroment.  This  study  aimed  to  know  distribution  and strucutre of mast cell on rat mesentery. The mesentery was stained with a 1 % safranine solution or toluidine blue  on  the  a  pepared  slide.  The  prepared  slides  were  immediately  viewed  by  a  observer  through  a microscope.  The  result  showed  that  mast  cells  stained  with  safranine  or  toluidine  blue  were  closely associated with postcapillary in the rat mesentery. Keywords : mast cell, mesentery